Negligence Of Customs and Excise in the Implementation of Judicial Decisions on Audit Result Disputes that can Cause Country Loss and Business Actors (A Study On Court Decision No. 46/Pk/Tun/2011 Which Has Not Been Done By Customs And Excise Till Nowadays) - Kiki Firmantoro (Research Collaboration Community (RCC), 2022)
Law enforcement has two instruments consisting of supervision and sanctions. In administrative law, supervision and sanctions are closely related to authority and are attached to the instrument of supervision. Law enforcement is the implementation of government functions in law enforcement. Therefore law enforcement must also heed the general principles of good governance. The law requires various devices with the aim of having good performance. One of the performances that distinguish it from the others is that the law has coercive rules, meaning that if the rule of law is poured into a statutory regulation, everyone must implement it. In this study, problems were formulated about (1) How to regulate Customs and Excise obligations in carrying out Supreme Court decisions that already have permanent legal force, (2) How to implement Supreme Court decisions against business actors, (3) How are legal provisions against administrative officials' decisions state for the decision. The decision of the Supreme Court must be carried out because if it is not, it will cause losses to the state. Court decisions that already have permanent legal force are orders that must be carried out. In this case, PT Multi Fabrindo Gemilang's practice of implementing the law is based on the description above: business actors should not be charged according to the Decree issued by the Director-General of Customs and Excise. The provisions of Article 26 paragraph (1) letter h of Law No. 17 of 2006 concerning Amendments to Law no. 10 of 1995 concerning Customs Jo. Article 2 and Article 3 of the Regulation of the Minister of Finance of the Republic of Indonesia No. 163/PMK.04/2007 dated December 17, 2007, concerning the Granting of Exemption from Import Duty on the Import of Goods by the Central Government or Regional Governments for the Public Interest.